‘SADHYATI’: An Integrated Platform for Medical Assistance - Chatterjee, Sumanta; Santra, Aniket; Chakraborty, Bishal; Chandra Saha, Nirmal (International Journal of Computer Sciences and Engineering, 2025)
In matters which involves life and death there is God and there are doctors. Doctors indeed are God to many of us. But looking at the other side of the coin many a time we see cases wherein a life is lost due to wrong diagnosis, which is too much a cost paid at the altar of human error. Then again we have cases where in a life is lost owing to the lack of awareness about certain fatal symptoms. Our approach here is to design a platform which caters to facilitate the aforesaid deficits. ‘Sadhyati’ shall serve as an E-community, which serves these deficits particularly in places where they lack. An easy to access and user friendly system that shall serve as the first step in terms of medical assistance. A platform for doctors as well as patients to interact irrespective of the socio-economic barriers that tends to exist.